2020
DOI: 10.37496/rbz4920190036
|View full text |Cite
|
Sign up to set email alerts
|

Feather and blood meal at different processing degrees in broiler pre-starter and starter diets

Abstract: The objective of this study was to evaluate the inclusion of feather and blood meal (FBM) in broiler pre-starter and starter diets according to the processing method used. Performance, digestibility, and intestinal morphometry of broilers fed diets containing FBM were evaluated in two experiments, in the pre-starter (1-7 d) and starter (8-21 d) phases in a randomized block design with four treatments and five replicates of 12 birds, totaling 20 experimental units per trial. The criteria used for block formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…On the contrary, the use of BM in feed for pigs and poultry is partially licensed, and its use in fish feed is fully approved. So far, the use of BM has been investigated not only in layers (Donkoh et al, 2001;Karunajeewa et al, 1989), broilers (Khawaja et al, 2007;Laboissière et al, 2020) and pigs (Kats et al, 1994;King'ori et al, 1998), but also in fish (Abery et al, 2002;Aladetohun & Sogbesan, 2013;Ding et al, 2020;Gao et al, 2020;Hatlen et al, 2013Hatlen et al, , 2015Martínez-Llorens et al, 2008). Based on previous studies on fish, 4%-9% BM can be included in the feed without any adverse effect on growth and feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the use of BM in feed for pigs and poultry is partially licensed, and its use in fish feed is fully approved. So far, the use of BM has been investigated not only in layers (Donkoh et al, 2001;Karunajeewa et al, 1989), broilers (Khawaja et al, 2007;Laboissière et al, 2020) and pigs (Kats et al, 1994;King'ori et al, 1998), but also in fish (Abery et al, 2002;Aladetohun & Sogbesan, 2013;Ding et al, 2020;Gao et al, 2020;Hatlen et al, 2013Hatlen et al, , 2015Martínez-Llorens et al, 2008). Based on previous studies on fish, 4%-9% BM can be included in the feed without any adverse effect on growth and feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Donkoh et al [ 49 ] observed improvements in growth performance of broiler chicks fed solar dried BM (7.5%) in combination with fish meal and without the inclusion of essential AA. Laboissiere et al [ 134 ] observed that a combination of FM and BM could be included in diets of broiler chickens at 9% in the pre-starter and starter phase without negative effects on performance and nutrient digestibility. However, processing methods for BM could reduce the nutrient utilization in broiler chickens.…”
Section: Protein-rich Feed Ingredientsmentioning
confidence: 99%
“…In animal feed, feather meal is used at a minimum level as it lacks methionine, tryptophan and histidine amino acids ( Luong and Payne 1977 ; Grazziotin et al, 2006 ). Despite the lowest digestibility values, variability of protein contents and bioavailability, feather meal proved as an important animal feed source ( Papadopoulos et al, 1986 ; Laboissière et al, 2020 ). One option to enhance digestibility might be hydrolysis with enzymes carried out by microbes that break down keratin substrates like bird feathers.…”
Section: Introductionmentioning
confidence: 99%